Perspectives on the Process of Negative Pressure Wound Therapy at Home in Patients With Chronic Wound: A Qualitative Descriptive Study. - Huang, Yao; Hu, Jiale; Mao, Beiqian; Ni, Pengwen; Shou, Yuyan; Hou, Lili; Xie, Ting (International Journal of Lower Extremity Wounds, 2022)
The purpose of this study was to explore the experience of negative pressure wound therapy (NPWT) at home among Chinese chronic wound patients. Qualitative descriptive study design was adopted, and qualitative data were collected through semistructured in-depth interviews. A purposive, sampling method was used. Informants were recruited from one single wound healing center of a teaching hospital and were interviewed following one course of NPWT at home. A thematic content analysis was undertaken in the framework of input-process-output theory to guide analysis. Of the 13 participants interviewed, 9 were female and 4 were male with an age ranging from 20 to 69 years. Two major categories with their corresponding codes were identified. The first, positive experience, had 6 codes: high-degree identity and feeling hope (input); easy operation and convenience (process); improvement of symptoms and effective treatment (output). The second category, negative experience, had 11 codes: high expenditure, defects of the NPWT device, health education deficiency, and lack of independence and rationales in making decision of NPWT (input); poor communication with wound professionals, unexpected circumstances, therapeutic side effects, and a change of self-image (process); impact on physical symptoms and daily life, impact on social activities, and impact on psychological well-being (output). Patients considered the NPWT at home as a promising regimen, but they also had a feeling of not being prepared and lack of health education to make medical decision independently. The participants' perceptions and experiences would provide valuable information to promote the intervention program of health education and advance service process optimization.